2015
DOI: 10.1007/s10120-015-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analyses of the safety and efficacy of ramucirumab in Japanese and Western patients in RAINBOW: a randomized clinical trial in second-line treatment of gastric cancer

Abstract: Background We evaluated the safety and efficacy of ramucirumab plus paclitaxel versus placebo plus paclitaxel in patients previously treated for advanced gastric or gastroesophageal junction adenocarcinoma in Japanese and Western subgroups from the RAINBOW trial. Methods Patients received ramucirumab at 8 mg/kg or placebo (days 1 and 15) plus paclitaxel at 80 mg/m 2 (days 1, 8, and 15 of a 28-day cycle). End points were compared between treatment arms within Japanese (N = 140) and Western (N = 398) populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 19 publications
4
50
0
Order By: Relevance
“…Multiple randomized trials have shown negative results for agents targeting EGFR, VEGF, MTOR, and hedgehog. To date, only two biologic therapies have been shown to improve overall survival in these patients: trastuzumab, a monoclonal antibody (mAb) targeting human epidermal growth factor 2 (HER2, ERBB2), and ramucirumab, a mAb targeting vascular endothelial growth factor receptor 2 (VEGFR2) (12)(13)(14)(15)(16)(17).…”
Section: Review Articlementioning
confidence: 99%
“…Multiple randomized trials have shown negative results for agents targeting EGFR, VEGF, MTOR, and hedgehog. To date, only two biologic therapies have been shown to improve overall survival in these patients: trastuzumab, a monoclonal antibody (mAb) targeting human epidermal growth factor 2 (HER2, ERBB2), and ramucirumab, a mAb targeting vascular endothelial growth factor receptor 2 (VEGFR2) (12)(13)(14)(15)(16)(17).…”
Section: Review Articlementioning
confidence: 99%
“…The incidence of gastric cancer in Japan was 131 893 in 2013, with 45 531 deaths from this disease in 2016 . Disparity in survival outcomes between patients from East Asia, including Japan, compared with those from the rest of the world has been observed in several clinical trials in advanced gastric cancer . For example, exploratory analyses from the AVAGAST study, a randomized phase III trial examining the addition of bevacizumab to capecitabine plus cisplatin in first‐line advanced gastric cancer, showed longer overall survival in patients from Asia (11.6‐14.1 months) compared with those from Eastern Europe/South America (7.3 months) or the USA/Western Europe (9.1 months) .…”
Section: Introductionmentioning
confidence: 99%
“…The Trastuzumab for Gastric Cancer (ToGA) trial revealed that trastuzumab, a recombinant monoclonal antibody against HER2 (also known as ERBB2), combined with fluoropyrimidine plus cisplatin provided a significant survival advantage compared with fluoropyrimidine plus cisplatin alone in patients with HER2-positive advanced GC [29,47,48] . The ramucirumab for patients with previously treated advanced gastric or gastro-esophageal junction [25,26,56,63] adenocarcinoma (RAINBOW) trial showed that the combination of ramucirumab and paclitaxel significantly improved overall survival compared with placebo plus paclitaxel and that this combination could be regarded as a new standard second-line chemotherapy for patients with advanced GC [49,50] .…”
Section: Current Treatment Of Gc and The Potential For Targeting Gcscsmentioning
confidence: 99%